Guest

question is in image

question is in image

Question Image
Grade:12

1 Answers

Harsh Patodia IIT Roorkee
askIITians Faculty 907 Points
7 years ago
Let log(4-x)= a and log(x + 1/2)=b
Above equation becomes

a2 + ab – 2b2
= a2 + 2ab- ab – 2b2
= a( a + 2b) – b(a +2b)
= (a-b)(a+2b)

\Rightarrow a=b or a= -2b
Put values and you can solve easily.
If there is any problem in that, reply on this thread.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free